2004
DOI: 10.2747/0272-3638.25.5.413
|View full text |Cite
|
Sign up to set email alerts
|

On The Waterfront: Globalization and Urbanization in Singapore

Abstract: Although many cities aspire to "global-city status," few have been as explicit as Singapore in its quest to create urban landscapes to project its global aspirations. This paper presents the case of the Singapore River development zone as a "hyper-symbol" of Singapore's global urbanism. By creating a world-class riverfront not unlike the acclaimed waterfronts of London, Sydney, or San Francisco, Singapore's urban planners hope to project the city as a venue worthy of world-class tourism and leisure activities,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
22
0

Year Published

2007
2007
2020
2020

Publication Types

Select...
7
2
1

Relationship

1
9

Authors

Journals

citations
Cited by 33 publications
(22 citation statements)
references
References 17 publications
(12 reference statements)
0
22
0
Order By: Relevance
“…It has been suggested that the uniformity of adaptive reuse projects modelled after foreign projects (such as Boston's Faneuil Market Place) has provoked public sentiment for local heritage (Chang et al, 2004). However, rather than a sense of dislocation among locals, the residents of Singapore have been flexible in the way they have responded to the internationalisation process.…”
Section: Resultsmentioning
confidence: 99%
“…It has been suggested that the uniformity of adaptive reuse projects modelled after foreign projects (such as Boston's Faneuil Market Place) has provoked public sentiment for local heritage (Chang et al, 2004). However, rather than a sense of dislocation among locals, the residents of Singapore have been flexible in the way they have responded to the internationalisation process.…”
Section: Resultsmentioning
confidence: 99%
“…Urban development is a result of an urban economic and institutional process at a given spatial‐temporal scale (Knox, 1994). Recent work on urban development in developing countries has suggested that urban development can be viewed as ‘a complex interplay of processes and agencies operating at different scales’ (Chang et al. , 2004: 415).…”
Section: Discussionmentioning
confidence: 99%
“…This has spurred local scholars to question the significance of globalisation for Singapore's urban landscape (see Heng and Chan, 2000;Chang, Huang and Savage, 2004;Hee, 2005a;Soh and Yuen, 2011). Such studies argue that, in the process of internationalising, industrialising and innovating, much of the intangible 'heartware' embedded in local places and practices are being replaced by modern hardware capable of usurping place identities and social memories.…”
Section: Urban Informality In a Global Citymentioning
confidence: 99%